Pendampingan Desain Perencanaan Pengembangan Kawasan Kolam Renang Desa Dukuh Kecamatan Tangen Kabupaten Sragen - Previari Umi Pramesti; Riza Susanti; Ratih Widiastuti (Jurnal Pengabdian Vokasi, 2023)
[Title: A design approach to developt the swimming pool area in Dukuh village, sub-district of Tangen, district of Sragen] Tourism activities are an inseparable part of societies and are expected to be the income for the regions. Dukuh village is one of the villages in the sub-district of Tangen, district of Sragen. Nowadays, Dukuh village attemps to develop its nature potencies which is one of them is the area of swimming pool. A design recommendation was proposed by the study programme of Civil Infrastructure Engineering and Architectural Design, Department of Civil and Planning, Vocational School, Diponegoro University, through a community service programme. There were three design approaches in this program. First, creating zoning of the swimming pool area by dividing the area into three main zones i.e. public, private, and services areas. Second, designing the landscape with hard and soft materials. Adding many trees in order to provide shaded areas for visitors. Third, providing good supporting facilities such as gazebo, sitting group, and cafeteria.